A clinical review of patients who underwent arthroplasty for the treatment of a neck of femur fracture at Chris Hani Baragwanath Academic Hospital - Wessels, Joseph Daniel (My University, 2022)
Background: Intracapsular neck of femur fractures are common in the elderly and are associated with significant morbidity and mortality. Little is known about the outcome of intracapsular neck of femur fractures in South Africa. The aim of this study was to determine the outcome of patients who underwent arthroplasty for the treatment of a neck of femur fracture at Chris Hani Baragwanath Academic Hospital. Methods: A retrospective, descriptive review was done on 114 patients who underwent arthroplasty for the treatment of a neck of femur fracture from 01 January 2013 to 30 April 2017 at Chris Hani Baragwanath Academic Hospital. Primary outcome measures included mortality and morbidity. Secondary outcome measures included patient based outcome scores, as well as clinician based outcome measures. Results: The mean age of the patients was 66.6 years (range 50 to 92 years). The majority of patients were female (n = 65; 59.1%). Most patients underwent an uncemented total hip arthroplasty (n = 80; 72.7%). The posterior approach was the most frequently used approach (n = 74; 67.3%). There was one (0.9%) in-hospital mortality and 19 (17.3%) patients had morbidities. Iatrogenic intra-operative peri-prosthetic fracture was the most frequently encountered complication, occurring in 14 (12.7%) patients. This did not alter the outcome. Conclusion: Our results show that patients have a favourable outcome when arthroplasty is used for the treatment of neck of femur fractures even though our management protocol differs from the recommended guidelines. Furthermore, our results indicate a low rate of morbidity with only one mortality.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Orthopaedic Surgery to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2022